Effect of Fatty Acids Fiber Concentration in Broiler Ration to Cholesterol, HDL and LDL Blood Serum - Hartoyo, B; Irawan, I; Iriyanti, Ning (ANIMAL PRODUCTION, 2005)
Cholesterol, HDL (High Density Lipoprotein) and LDL (Low Density Lipoprotein) in blood serum of broiler could can be controlled by food manipulation using different fatty acids and fiber content in ration. This research was planned to study the influence of fat i.e. cis-trans fatty acids and raw fiber content on feed to cholesterol, HDL and LDL biosynthesizing broiler blood serum. The research model was experimental and the design used was Completely Randomized Design in factorial pattern 2 x 3. The first factor was type of fat (L) : L1= cis fatty acid and L2 = trans fatty acid. The second factor was fiber content in feed (S) i.e. S1 = 5% ; S2 = 7%, and S3 = 9%. Each treatment was repeated four times, it means 24 observation. Variables observed were : cholesterol, HDL, LDL concentration in blood serum of broiler. The result indicated that the use of 5 % palm kernel oil and 5 % tallow fat in feed containing 5 %, 7 % and 9 % fiber respectively have unsignificant result (P>0.01) to cholesterol and LDL blood serum of broiler, but have significant to HDL concentration (P<0.01). The average cholesterol of blood serum was between 76.46 mg/dl (L2S3) to 99.88 mg/dl (control), HDL concentration was 21.19 mg/dl (L2S1) to 38.85 mg/dl (control), and LDL concentration was 46.83 mg/dl (L2S2) to 61.14 mg/dl (control). It can be concluded that feeding with far in the form of cis (palm kernel oil) or trans (tallow) when combined with proporsional fiber addition can be used as feed because it does not increase the cholesterol and LDL in broiler blood. The reduction of cholesterol as much as 23.53 % in control feed was found in treatment with 5 % tallow addition in combination with 9 % raw fiber content, HDL concentration was higher in treatment with palm kernel oil compared to tallow addition. (Animal Production 7(1): 27-33 (2005)Â Key Words : Cholesterol, HDL, LDL, Cis Fatty Acid, Trans Fatty Acid